Process engineering addressing the gap between study and chemical industry - Kleiber, Michael (De Gruyter Textbook, 2024)
"Reading the book, you can feel the long practical experience of the author. The text is easy to read, even where concepts can be complex. The strong theoretical background of the author is well known from other publications. In this book, however, the topics are presented on a level that every engineer and scientist in the chemical industry and process industry should know and can understand. This book would have been very helpful at the beginning of my career to close the addressed gap. Therefore, I can strongly recommend it not only to all students close to their degree, but also to engineers and scientists just starting their industrial career in the related industrial sectors that are subsumed under the term process industry (chemical or petrochemical industry, pharmaceutical industry, food industry, biochemical industry, environmental technology, etc.). The book is like an investment. Doing a better job and getting a better job evaluation might pay for the book ..." Prof.